Maritime challenges and priorities in Asia : implications for regional security - Ho, Joshua; Bateman, W. S. G. (Walter Samuel Grono) (New York : Routledge, 2012)
"Maritime issues are particularly important for Asian countries, where there is a high reliance on shipping routes for international trade, many difficult disputes over maritime boundaries, and the prospect of increasing tensions where maritime power might play a significant role. This book provides a comprehensive survey of the maritime issues affecting Asia."--Publisher's description.
Managing good order at sea in the Asia-Pacific / Sam Bateman -- The historic attributes of the sea and maritime developments in the Asia-Pacific / Geoffrey Till -- Carriage capacity of the Straits of Malacca and Singapore / Yee Cheok Hong -- Indonesia's maritime challenges and priorities / Hasjim Djalal -- Malaysia's maritime challenges and priorities / Mohd. Nizam Basiron -- Myanmar's maritime challenges and priorities / Maung Aung Myoe -- Maintaining good order at sea : maritime challenges and priorities in the Philippines / Mary Ann Palma -- Singapore's maritime interests / Joshua Ho -- Thailand's maritime challenges and priorities / Wilfried Herrmann -- Good order at sea : challenges and priorities of Vietnam / Nguyen Hong Thao -- China's maritime security : priorities and challenges / Wang Dong and Jiang Xin -- Japan's maritime challenges and priorities / Tetsuo Kotani -- Korea's maritime challenges and priorities / Seokwoo Lee -- America's maritime challenges and priorities : the Asian dimension / James Kraska -- Australia's maritime challenges and priorities : recent developments and future prospects / Robin Warner -- Maritime challenges and priorities in Asia : an Indian perspective / Prabhakaran Paleri -- New Zealand's maritime challenges and opportunities / Joanna Mossop -- Conclusion : identifying common maritime challenges and priorities / Sam Bateman.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sea-power -- Asia; Marine resources -- Asia; National security -- Asia; Electronic books